The Influence Of The Financial Performance Of The Stock Price Banking Companies Listed In Indonesia Stock Exchange Period 2010-2014 - lin Ahmad Zarkasi; Indah Lia Lia Puspita (Universitas Malahayati, 2016)
Abstrack: Investors need information that is understandable, relevant, reliable and comparable in evaluating the financial position and performance of the bank as well as useful in making investment decisions. This study aimed to analyze the effect of capital with Capital Adequacy Ratio (CAR) as indicator, asset quality with non performing loans (NPL) as indicator, profit with Return on Assets (ROA) as indicator and liquidity with Loan to Deposit Ratio (LDR) as indicator on Stock Price banking companies listed in Indonesia Stock Exchange 2010-2014. Data obtained from the Financial Statements issued by Bank Indonesia and the time period of 2010 to 2014. Amount of this study population was 20 companies and the total sample of 5 companies with a purposive sample passing phase. Analysis techniques that will be used in this study is a multiple linear regression to obtain a comprehensive result of the relationship between one variable with another variable. The results showed that the variable Capital Adequacy Ratio (CAR), Return on Assets (ROA), Non-Performing Loans (NPL) have positive effect on banking stock price, while the, loan to deposit ratio (LDR) and BOPO have negative effect on banking stock price. Simultaneously test results indicate there is influence between CAR, ROA, NPL, LDR and BOPO together to the banking company's stock price that go public in Indonesia Stock Exchange. The magnitude of the effect was 67,7% while the remaining 32,3% influenced by factors other than research or outside the regression equation.